A critical review on value co-creation: towards a contingency framework and research agenda. Issue 2 (7th June 2019) - Wang, Xueqin; Wong, Yiik Diew; Teo, Chee-Chong; Yuen, Kum Fai
Abstract : Purpose: Although a dominant marketing concept, value co-creation (VCC) is not without controversy. Inspired by value co-destruction (VCD), the purpose of this paper is to review the scattered literature on the uncertainties in collaborative value formation, synthesising contingency factors of value outcomes in VCC. Design/methodology/approach: The paper is based on an examination of 84 peer-reviewed journal articles. Recognising the drawbacks of the macroscopic abstraction in existing the VCC literature, the authors adopt a zooming-in approach to identify distinct patterns of contingency factors in the collaborative value-formation process. Findings: From a macro-social perspective, VCC may connote a sense of exploitation of "consumers" and a need for consumer control of "producers", impeding harmonious value formation. Zooming into actor-to-actor interactions, the collaborative relationship is found to be a source of uncertainties in value formation, which is further complicated by differences in the knowledge intensities of services. Finally, reviewing the individual consumer reveals a most nuanced picture that demonstrates heterogeneities of consumers' VCC involvement and complexities in their perceptions and behaviours. Five propositions and a contingency framework are proposed. Research limitations/implications: Six value formation mechanisms are proposed based on interconnected and multi-level perspectives, providing implications for managers and future researchers. Originality/value: This paper contributes to rebalancing VCC research by synthesising insights on the potential contingencies, which are relatively under-explored yet vital to keep the controversy alive and relevant, and re-invigorating business processes.